Recent Developments in Dividend Policy: Evidence from Indonesia - Aning Fitriana; Aqlima Cendera Dewi; Doddy Setiawan (University of Merdeka Malang, 2018)
This study aims to describe the development of dividend policy research in Indonesia. This study analyzes 7 accreditation journals in Indonesia from 2002 – 2017 periods, there are 35 articles discussing dividend policy. We have classified this article based on topics, research methods, models used, and descriptions of research results in Indonesia. The result obtained is mostly published in Jurnal Keuangan dan Perbankan (JKP) 11 articles out of 35 articles. The most of the studied antecedent topics are financial ratios, ownership structures, and capital structures while for the most consequences topic is firm value. Overall, this research uses an analytical method and the measurement of dividend policy most use dividend payout ratio. This research period in the articles ranged from an average of 5,5 years. This research aimed to give perspective about researches that have been done in Indonesia about dividend policy and the research result can be used as a reference for next research or others such as investor and practitioners.JEL Classification: G30, G35DOI: https://doi.org/10.26905/jkdp.v22i1.1799